Knowledge, attitude and practice on stroke among hypertensive patients attending Medical Outpatient Department of Hospital Tengku Ampuan Afzan - Sowtali, Siti Noorkhairina; Ibrahim, Nor Izzati (2019)
Stroke is ranked as the second leading cause of mortality and the third leading cause of disability despite advancement in diagnostic and treatment regime (Johnson, Onuma, Owolabi & Sachdey, 2016). In Malaysia, stroke is recognized as the third leading cause of death after ischemic heart disease and pneumonia (Zariah et al, 2015). According to Hamidon et al (2012), it is important to emphasize on primary intervention; health education especially for those at higher risk for stroke attack in order to reduce stroke incidence. However, there is limited information regarding knowledge, attitude and practice towards stroke in Malaysia and limited study conducted in Hospital Tengku Ampuan Afzan (HTAA), Kuantan, Pahang.